Visual perception training: cutting edge psychophysics and 3D technology applied to sport science - Beauchamp, P.; Mindroom, P. (High Performance SIRCuit, 2011)
This article will outline new training technology for enhancing perceptual-cognitive skills of athletes achieved through training with a 3D "cave. environment. CogniSens Athletics (www.cognisensathletics.com) specializes in applying neurobiological science and technology for performance applications in the sports, medical and military environments. The science behind the technologies (Neurotracker, Neurominder and NeuroBalance) has been developed by Dr. Jocelyn Faubert and his team. Dr. Faubert is Director of the "Visual Psychophysics and Perception Laboratory. based at the University of Montreal. These technologies are designed for both performance enhancement and concussion management. NeuroTracker can be used for a) performance enhancement, b) reduced risk of injury, and c) as a baseline reference for post-concussion return-to-play protocol: a) Performance enhancement: NeuroTracker is a unique perceptual-cognitive training device to improve athletic performance. NeuroTracker trains an athlete to absorb and process complex movement and distribute his attentional resources throughout the visual field. The trained athlete will decrease his response time during play action and increase time available to make decisive decisions. b) Reduction of risk of injury: with improved peripheral vision awareness, the athlete can anticipate avoidable collisions and thereby reduce risk of injury c) Baseline reference for post concussion Return-to-Play decision: NeuroTracker maps and stimulates high-level cognitive functions directly related to performance. The baseline reference of the healthy athlete provides the target Return-to-Play objective reference to ensure the athlete is fully recovered from his concussion injury, thereby reducing the risk of recurring concussions.